Development and quality evaluation of low fat functional paneer - Kavya Kuttan; K. Radha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An experiment was conducted to utilize skim milk for the preparation of low fat paneer, a value added product. Low fat paneer was prepared by using whey protein concentrate (WPC) and inulin as fat replacers. Full fat control paneer (C1) was prepared from buffalo milk standardized to 5 per cent fat and 9 per cent SNF. Skim milk control paneer (C2) was prepared from skim milk standardized to 0.3 per cent fat and 9 per cent SNF. WPC was incorporated at 0.25 (T1) and 0.5 per cent levels (T2). Inulin was used at the level of 1.5 (T1) and 2 per cent (T2) for the preparation of low fat paneer. The prepared paneer samples were evaluated for physico-chemical, microbiological and organoleptic qualities. Incorporation of WPC had significantly increased the yield as well as moisture content of low fat paneer. Inulin at 2 per cent level had increased the yield of low fat paneer. Both WPC and inulin had improved the sensory acceptability of low fat paneer prepared from skim milk.